Dissolution of Islamic Community Organizations (Ormas) in the Context of a State of Law and a Democratic State - Suteki Suteki; Abdul Jalil (Universitas Islam Negeri Walisongo Semarang, 2021)
Community organizations (Ormas) in a country are evidence of the existence of democracy in a country. Indonesia is a constitutional state as well as a democratic state according to Article 1 Paragraphs 2 and 3 of the 1945 Constitution. The existence of mass organizations is recognized and protected in Indonesia as part of the state's recognition of the rights of every citizen to freedom of association and assembly. The dissolution of CSOs carried out without court procedures, according to the author, is a violation of the concept of the rule of law adopted by Indonesia as well as the castration of the rights of association, assembly, and expression of opinion in a democratic country. This study uses a socio-legal approach, with analytical descriptive research methods. Sources of data used are primary data in the form of interviews. The primary legal materials used in this research are the Law on Ormas; and SKB concerning the Prohibition of Activities Using Symbols and Attributes and Termination of FPI Activities. The results of the study stated that the disbandment of mass organizations was politically and ideologically motivated, namely differences in political attitudes and aspirations between Islamic organizations and the government. The dissolution of mass organizations is the impact of the applied procedural democracy. Democracy is not practiced substantially, in a democratic climate, differences in aspirations are a necessity. The disbandment of mass organizations has an impact on disharmony relations between religion and the state, between religious adherents and the government, and has the potential to cause polarization in society. The direct impact of the disbandment of Islamic organizations is the difficulty of building a synergistic relationship between religion and the state, between religious adherents and the government.[]Organisasi kemasyarakatan (Ormas) di suatu negara adalah bukti hidupnya demokrasi di sebuah negara. Indonesia adalah negara hukum sekaligus negara demokrasi sesuai Pasal 1 Ayat 2 dan 3 UUD 1945. Keberadaan Ormas diakui dan dilindungi di Indonesia sebagai bagian bentuk pengakuan negara atas hak setiap warga negara atas kebebasan berserikat dan berkumpul. Pembubaran Ormas yang dilakukan tanpa prosedur pengadilan menurut penulis adalah menyalahi konsep negara hukum yang dianut oleh Indonesia sekaligus pengkebirian hak-hak berserikat, berkumpul, dan menyatakan pendapat di negara demokrasi. Penelitian ini menggunakan pendekatan socio-legal, dengan metode penelitian deskriptif analitis. Sumber data yang digunakan adalah data primer yang berupa hasil wawancara. Bahan hukum primer yang digunakan dalam penelitian ini adalah UU tentang Ormas; dan SKB tentang Larangan Kegiatan Penggunaan Simbol dan Atribut Serta Penghentian Kegiatan FPI. Hasil penelitian menyatakan, pembubaran ormas dilatarbelakangi politis dan ideologis, yakni perbedaan pandangan sikap politik dan aspirasi antara ormas Islam dengan pemerintah. Pembubaran ormas merupakan imbas dari demokrasi prosedural yang diterapkan. Demokrasi tidak dipraktikkan secara substansial, dalam iklim demokrasi perbedaan aspirasi adalah keniscayaan. Pembubaran ormas berdampak pada hubungan yang disharmoni antara agama dengan negara, antara pemeluk agama dengan pemerintah, dan berpotensi menimbulkan polarisasi di tengah masyarakat. Dampak langsung dari pembubaran ormas Islam adalah kesulitan membangun relasi sinergi antara agama dengan negara, antara pemeluk agama dengan pemerintah.Â